Peningkatan Keaktifan Siswa Dalam Pembelajaran Matematika Melalui Pendekatan Kolaboratif - Nengah Darmajaya; Ahmad Zainul Irfan (Alpatih Harapan Semesta, 2025)
Improving student engagement in learning mathematics is a major challenge in education today. This study aims to explore the effectiveness of a collaborative approach in active learning methods to increase student engagement. The method used is classroom action research, which involves cycles of planning, implementation, observation, and reflection. The results showed that the implementation of the collaborative approach was able to significantly increase student participation, measured through observations and questionnaires administered before and after the intervention. Students showed increased motivation and cooperation in groups, as well as better understanding of mathematical concepts. The implications of this study can be used as a reference for educators to implement more interactive and collaborative learning methods, thus creating a more dynamic and enjoyable learning environment. This research is expected to make a positive contribution to the development of mathematics teaching methods in schools.